Tumor Necrosis Factor-α is Inversely Related to Free Thyroxine in Euthyroid Subjects Without Diabetes - van Tienhoven-Wind, L. J. N.; Dullaart, R. P. F. (Hormone and Metabolic Research, 2017)
Lower thyroid functional status within the euthyroid range may confer increased atherosclerosis susceptibility, as evidenced by increased intima media thickness and coronary artery calcification. Associations of lower thyroid functional status with pro-atherogenic (inflammatory) biomarkers may also extend into the euthyroid range. Here we established relationships of plasma tumor necrosis factor-α (TNF-α) with thyroid stimulating hormone (TSH) and free thyroxine (free T4) in euthyroid subjects with and without Type 2 diabetes mellitus (T2DM). Fasting TSH, free T4, and TNF-α were measured in 81 nondiabetic subjects and in 73 T2DM subjects with Type 2 diabetes mellitus (T2DM; insulin using subjects were excluded) with TSH and free T4 levels each within the institutional reference ranges. TSH was similar and free T4 was slightly higher in T2DM (p<0.016). Plasma TNF-α was increased in T2DM (p=0.007). In nondiabetic subjects, TNF-α was correlated inversely with free T4 (r=−0.254, p=0.022), whereas such a relationship was absent in T2DM subjects (r=0.058, p=0.63). Multivariable linear regression analysis showed that in nondiabetic subjects TNF-α remained inversely associated with free T4 after adjustment for age and sex (β=−0.243, p=0.032) and additionally for thyroid autoantibodies (β=−0.251, p=0.027), contrasting the lack of relationship in T2DM subjects (interaction: p=0.053). In T2DM subjects, TNF-α was also unrelated to free T4 taking account of possible confounders, as well as after exclusion of subjects using metformin or antihypertensive medication. In conclusion, higher levels of TNF-α relate to lower free T4. Low-normal thyroid function could influence pro-inflammatory pathways. This relationship appears to be disturbed in T2DM.
Keywords: tumor necrosis factor-α; thyroid function; Type 2 diabetes mellitus